Belimbing Wuluh (Averrhoa bilimbi Linn.) Leaf Powder as the Natural Repellent Against Meat Fly (Genus sarcopaga) - Wahyuni, Denai; Sari, Wulan (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Efforts are often made to control meat flies with chemical insecticides, but they harm humans, the environment, and other organisms. We use belimbing wuluh leaf as a natural repellent in controlling meat flies. The purpose of this study is to determine the effect of belimbing wuluh leaf powder as a natural repellent and the number of effective doses against meat fly. Using 15 samples at each dose of 1 gr, 2 gr, 3 gr, 4 gr, 5 gr, negative control without powder, positive control with Top Killer powder, performed four repetitions every 10 minutes of observation for 60 minutes. Kolmograv-Smirnov normality test, P-value 0.200 0.05 means that the data for each group is normally distributed. Variant test, P-value 0.066 0.05, so there was a group that had homogeneous data variants, an ANOVA test resulted in a Sign value of 0.001. There is an effect of the belimbing wuluh leaf powder dose as the repellent of meat flies. The 5-gram dose is the most effective as a natural repellent of meat flies (Genus Sarcopaga).